INOVASI PRODUKSI DAN DESAIN PADA INDUSTRI TENUN TROSO JEPARA - Jati Widagdo; M Rifqy Roosdhani; Mujiyono; Nimas Aulia Pambajeng Miftahunnajah (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2025)
This community service program was implemented in Troso Village, Pecangaan District, Jepara Regency, known as a center for ikat weaving. The Troso weaving industry has significant economic and cultural contributions, but faces various challenges, including low production capacity due to the use of traditional handlooms (handlooms), dependence on environmentally unfriendly synthetic dyes, and a lack of distinctive motifs that can strengthen local identity. This activity aims to increase productivity, introduce environmentally friendly technology, and develop new motifs based on local culture. The implementation method includes five stages: socialization, training in the use of natural dyes, the application of mechatronic handloom technology, training in designing distinctive motifs, and production assistance. The program results show a two-fold increase in production capacity, the use of more environmentally friendly natural indigovera and secang dyes, and the creation of distinctive motifs inspired by Jepara’s coastal culture. In addition to impacting the artisans’ economy, this activity also strengthens local cultural identity and supports the sustainability of Troso Village as a center for creative industries. Thus, production and design innovation has proven to be an effective strategy in strengthening the competitiveness of Troso weaving in both domestic and international markets.